Najib’s Mother of All Budgets: Gearing Up For 14th General Election - Saleem, Saleena (2017)
The Najib government’s Budget for 2018 is widely seen as a feel-good package geared for the upcoming general election. This contrasts with the opposition coalition’s emphasis on good governance in its Alternative Budget. Which will win the public vote?